B131 Patient experience and recovery following regional anaesthesia for arteriovenous fistula surgery. (11th August 2022) - Bhattacharyya, S; Ali, Y; Devlin, A
Abstract : Background and Aims: Arteriovenous fistulae (AVF) remain the gold standard vascular access for haemodialysis (HD) in end-stage renal failure (ESRF) patients. Operatively they can be formed under local anaesthesia (LA), regional anaesthesia (RA) and general anaesthesia (GA). RA may confer several advantages, including AVF patency benefits compared to LA [1] and decreased hospital admission compared to GA [2]. However, RA may not be the anaesthesia modality preferred by patients. Currently our service allows a combination of LA, RA and GA, depending on patient selection and staff skill mix. We aim to explore patient experience and recovery and evaluate our service, in the RA arm. Methods: We surveyed patients that consented over a one month period prospectively, using the Quality of Recovery 15 (QoR-15) questionnaire following AVF formation under RA, a tool validated for analysis of post-operative recovery. Since each patient's experience is unique, we also supplemented the QoR-15 with three additional free text questions: 1. What did you think about your anaesthetic/nerve block?; 2. What was good about your anaesthetic/nerve block?; 3. What was bad about your anaesthetic/nerve block?. Results: There was a high frequency of 0/10 answers to questions 11. and 12. about moderate and severe pain in the 24 hours post-surgery. In addition, patients reported being pleasantly surprised by the experience, including being "very smooth" and being "able to joke" with the team. Conclusions: RA may be a good option for patients undergoing AVF formation, despite possible pre-conceptions. We aim to increase our sample size in order to better validate our results.